The Mechanism of a Careless Crime (on an Example of Road Transport Offences) - BAKISHEV, Kairat A. (Journal of Advanced Research in Law and Economics; Vol 9 No 5 (2018): JARLE Volume IX Issue 5(35) Fall 2018, 2018)
The mechanism of a careless crime is different from the mechanism of an intentional crime. Its peculiarity lies in the fact that in careless crimes the severity of the harmful consequences is determined by the nature of the situation, the used instruments and the means of the crime whereas in an intentional crime this burden, as well as the situation and the instrument (means), depending on the will of the subject. Elements of the mechanism in the criminological doctrine are: (a) criminal personality; (b) the situation of a crime; (c) the instrument (means) of a crime. The mechanism also includes the motivation and victim of a crime. It is established that the imprudent criminal is characterized by motives that are not characteristic of the person who committed the crime intentionally. Each form of guilt is characterized by a certain group of motives, which requires establishment in each specific case. Measures to counteract careless crime should be developed taking into account the factor of the victim of the crime. Illegal behavior of the victim is often caused by his negative attitudes and habits. This indicates that the processes of criminalization and victimization are interrelated. The role and nature of interaction with each other are different and the significant predominance of one of them can be considered the main cause of the crime. On this basis the author offers his edition of the mechanism of a careless crime.